2016
DOI: 10.7874/jao.2016.20.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Acute Low-Tone Sensorineural Hearing Loss According to Treatment Modality

Abstract: Background and ObjectivesWe compared improvements in hearing thresholds in acute low-tone sensorineural hearing loss (ALHL) patients after two different treatments: steroid alone and steroid and diuretic combined. We analyzed how the duration between the onset of symptoms and the initiation of treatment affected hearing loss improvement and investigated the relation between presence of vertigo in ALHL patients and ALHL progression to Ménière's disease (MD).Subjects and MethodsWe retrospectively analyzed the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
8
0
3
Order By: Relevance
“…However, as the cochlear hydrops progresses to the vestibular organs, patients with endolymphatic hydrops may experience dizziness, and ALHL progresses to Ménière disease. 4,14,15 Jinkyung et al 14 found that ALHL patients with vertigo had a higher possibility of developing Ménière disease (40%) than those without vertigo (12%). At present, the relationship between ALHL and Ménière disease is not fully understood, and relevant research is still needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the cochlear hydrops progresses to the vestibular organs, patients with endolymphatic hydrops may experience dizziness, and ALHL progresses to Ménière disease. 4,14,15 Jinkyung et al 14 found that ALHL patients with vertigo had a higher possibility of developing Ménière disease (40%) than those without vertigo (12%). At present, the relationship between ALHL and Ménière disease is not fully understood, and relevant research is still needed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are the main drugs that are generally used to treat ISSNHL [ 13 14 ]. The action of steroids is uncertain, but they can be beneficial for infectious, inflammatory, and immune-mediated diseases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Menurut Chang pemberian kortikosteroid bisa tunggal atau kombinasi dengan. 12 Chang menyimpulkan bahwa pemberian kortikosteroid dapat menjadi pilihan untuk terapi jangka pendek pada pasien ALHL. 12 Menurut Oishi metilprednisolon diberikan dengan dosis 30-60 mg/hari sebagai dosis awal.…”
Section: Telah Dilaporkan Kasus Dengan Diagnosisunclassified
“…12 Chang menyimpulkan bahwa pemberian kortikosteroid dapat menjadi pilihan untuk terapi jangka pendek pada pasien ALHL. 12 Menurut Oishi metilprednisolon diberikan dengan dosis 30-60 mg/hari sebagai dosis awal. 5 Sedangkan Choi16 memberikan metilprednisolon 40 mg pada hari 1-3, 30 mg pada hari 4-6, 20 mg pada 7-9 dan 10 mg pada hari 10-12.…”
Section: Telah Dilaporkan Kasus Dengan Diagnosisunclassified
See 1 more Smart Citation